Quem sou - Sanches, Silvane Souza Meneses; Silva, Viviane Souza; Silva, Kerlia Pereira; Guimarães, Renata Maria de Sousa; Lopes, Cleuza Francisca da Silva; Lima, Maria dos Santos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf